Are payroll tax cuts absorbed by insiders? Evidence from the Swedish retail industry - Hans Seerar Westerberg (Institute of Retail Economics (HFI), 2021)
It is commonly argued that payroll tax cuts are inefficient for increasing employment among outsiders because insiders will use their power to bargain for higher wages at the expense of outsiders' possibility of becoming employed. The extent to which insiders or outsiders reap the rewards of payroll tax cuts is a longstanding issue, and previous literature has largely focused on the employment effects of outsiders. Using wage statistics of employees in the Swedish retail sector, we investigate the effects of a youth payroll tax cut in 2007 on insiders' wage earnings and the number of hours worked. In accordance with earlier studies, the results show that the payroll tax cut increased insiders' total wage earnings. However, only 21 percent of the increase in wage earnings was a result of higher bargained wages, 57 percent of the wage increase corresponds to a higher intensive margin of employment, and the rest was attributed to the number of hours worked by insiders with a higher hourly wage rate. There is, thus, little to suggest that insiders can absorb large amounts of payroll tax cuts in the form of higher bargained wages, even in the case of a small number of workers with the most bargaining power.
Keywords: D24; L25; L26; 330; Retail; labor market; wage; payroll tax; DiD; employment; inconvenience allowance